Unveiling Pandemic Metaphors : A Critical Analysis of Christina’s The End Of Men - Indra Indra; Diah Supatmiwati; Zainuddin Abdussamad (Riviera Publishing, 2025)
This research aims to analyse metaphors which appear from Amanda Maclean as main character in The End of Men Novel. Metaphors that used in the work as representation of chaos condition because of Pandemic was happening in the story. Theory which used in this research from George Lakoff. He gives understanding that metaphor is not just as stylistic in the linguistic’s concept but it reflects thoughts and experiences of characters. He argues that metaphor divided into three type, they are structural metaphor, orientational metaphor and ontological metaphor. This is qualitative descriptive research, means each data would be described deeply. The data source from a novel titled The End of Men by Christina Sweeney-Baird. Data are taken from words, sentences and quotations from the novel. This research focus to analyse metaphors that appear in the work and describe them with Lakoff theory. Research question in this research is what are kinds of metaphor that used in the novel ? The result of this study, there are two kind of metaphor appear in the novel, the are structural and ontological metaphor. Second, the meaning of structural type show that characters in the novel present another terms to communicate their purpose and condition. In other hand, ontological metaphor gives understanding about abstract of mind.